An Au–Cu bimetal catalyst for acetylene hydrochlorination with renewable γ-Al2O3 as the support. Issue 22 (6th February 2015) - Zhao, Jigang; Zeng, Junjian; Cheng, Xiaoguang; Wang, Lei; Yang, Henghua; Shen, Benxian
Abstract : The bimetal catalyst gold(iii ) chloride–copper(ii ) chloride (AuCl3 –CuCl2 ) was prepared with different gamma-aluminium oxide (γ-Al2 O3 ) supports and its catalytic properties towards acetylene hydrochlorination were assessed in a fixed-bed reactor. Abstract : The bimetal catalyst gold(iii ) chloride–copper(ii ) chloride (AuCl3 –CuCl2 ) was prepared with several different gamma-aluminium oxide (γ-Al2 O3 ) supports and its catalytic properties towards acetylene hydrochlorination were assessed in a fixed-bed reactor. The comparison indicated that one of the catalysts attained the highest activity with an acetylene conversion of 97%, which was far higher than the others. Catalysts were characterized using detailed X-ray diffraction, nitrogen-Brunauer, Emmett and Teller surface area analysis (N2 -BET), ammonia temperature-programmed desorption, Fourier-transform infrared spectroscopy and carbon dioxide temperature-programmed desorption analysis. It is proposed that the base site contributed to its high catalyst activity compared with the other catalysts, instead of the acid site or the textural properties on the support, therefore, the activity and the life of the catalysts can be improved significantly by treating the supports with potassium hydroxide. In addition, the results of N2 -BET, thermogravimetric analysis and scanning electron microscopy indicated that the catalysts deactivated rapidly because of carbon deposition, and the actual amount of coke deposition was 18.0% after the reaction. AuCl3 –CuCl2 /γ-Al2 O3 was easily regenerated for reuse as a catalyst by burning off in an air atmosphere for 10 min. The activity of the regenerated catalyst nearly reached the level of the fresh catalyst.